The Linguistic Atlas of the East of Guilan on the Basis of Morphological Analysis (Lexical - Inflectional) - Afshar, Maryam Mahlouji; Kalbassi, Iran (JOURNAL OF ADVANCES IN LINGUISTICS, 2016)
This article, in line with â€œThe National Project of the Dialectologyâ€, aims to provide a linguistic atlas in the East of Guilan province. Due to the large number of speakers in the southern edge of the Caspian Sea and many differences between dialects and accents, this area has great importance linguistically and providing the linguistic atlas in representation and introduction of dialects in this land can be an important achievement to access the indigenous, cultural, social and historical studies among linguistics and persons who are interested in culture. In order to achieve this principal issue, there has been investigated the morphological differences and similarities (lexical - inflectional) of language varieties in the East of Guilan province with the standard Persian- even more than phonetic and syntactic analysis- and they can have the principal role in providing the linguistic atlas. So in this article, through presenting the morphological evidences (lexical - inflectional) and comparing them with standard Persian, there has been marked a dialect with different accents- the Guilaki dialect from the East of Guilan province and it has been depicted for linguistic atlas. The study was conducted by library and field method and by collecting data from a questionnaire consisting of 100 words and sampling from 20 villages in the East of Guilan province- from Astaneh Ashrafieh to the end of the eastern border of Guilan province (Chaboksar). The data obtained by each village has been considered in the tables related to each word and has been moved on the map of region after comparing with the standard Persian and finally the linguistic atlas has been made. To achieve genuine accents, the speakers of middle-aged who spent much of their life in the area have been helped and villages have been considered with more phonetic differences in accent.